Services of SageMathCloud environment and their didactic potential in learning of informatics and mathematical disciplines - Pavlo V. Merzlykin; Maiia V. Popel; Svitlana V. Shokaliuk (Academy of Cognitive and Natural Sciences, 2018)
In the article are reviewed the questions of expedient using SageMathCloud environment, as an integrator of services that can be used during different kinds of learning activities. Research goals: identify the structural elements of the SageMathCloud environment, that it is appropriate to use the in learning informatics and mathematical disciplines. Research objectives: consider the structure of the kernel of SageMathCloud environment; highlight the structural elements, that can be used in learning informatics and mathematical disciplines and explore the possibility of their use. Object of research: computer oriented study of informatics and mathematical disciplines. Subject of research: use structural elements of the SageMathCloud environment in learning informatics and mathematical disciplines. Research methods used: analysis of SageMathCloud environment, comparison of the structural elements of the environment and their generalization according to informatics and mathematical disciplines. In the work analyzed, generalization and systematization of the major structural elements of the cluster SageMathCloud, reviewed the characteristics of items that can be used in the study informatics and mathematical disciplines. Results of the research will be used for improve methods of computer based learning of informatics and mathematical disciplines.